Synergistic integration of metal nanoclusters and biomolecules as hybrid systems for therapeutic applications - Peng Gao; Xin Chang; Dagan Zhang; Yafei Cai; Gen Chen; Hao Wang; Tianfu Wang (Elsevier, 2021)
Therapeutic nanoparticles are designed to enhance efficacy, real-time monitoring, targeting accuracy, biocompatibility, biodegradability, safety, and the synergy of diagnosis and treatment of diseases by leveraging the unique physicochemical and biological properties of well-developed bio-nanomaterials. Recently, bio-inspired metal nanoclusters (NCs) consisting of several to roughly dozens of atoms (<2 nm) have attracted increasing research interest, owing to their ultrafine size, tunable fluorescent capability, good biocompatibility, variable metallic composition, and extensive surface bio-functionalization. Hybrid core-shell nanostructures that effectively incorporate unique fluorescent inorganic moieties with various biomolecules, such as proteins (enzymes, antigens, and antibodies), DNA, and specific cells, create fluorescently visualized molecular nanoparticle. The resultant nanoparticles possess combinatorial properties and synergistic efficacy, such as simplicity, active bio-responsiveness, improved applicability, and low cost, for combination therapy, such as accurate targeting, bioimaging, and enhanced therapeutic and biocatalytic effects. In contrast to larger nanoparticles, bio-inspired metal NCs allow rapid renal clearance and better pharmacokinetics in biological systems. Notably, advances in nanoscience, interfacial chemistry, and biotechnologies have further spurred researchers to explore bio-inspired metal NCs for therapeutic purposes. The current review presents a comprehensive and timely overview of various metal NCs for various therapeutic applications, with a special emphasis on the design rationale behind the use of biomolecules/cells as the main scaffolds. In the different hybrid platform, we summarize the current challenges and emerging perspectives, which are expected to offer in-depth insight into the rational design of bio-inspired metal NCs for personalized treatment and clinical translation.